The treatment of journalistic content and its influence on the reputation of the Spanish press: the november 2019 election campaign as case study - Barbeito Veloso, María Luz; Perona Páez, Juan José; Rodríguez Prieto, Victoria; Hernández Ruiz, Alejandra (Estudios sobre el Mensaje Periodístico, 2020)
The research follows the aim of confirming to what extent there is a correlation between Spanish press´s contents and the reputation among audiences related to these media outlets. From the notion of reputation which underlines variables like credibility,informative rigour, journalistic quality and also professional ethics and deontology, the present content analysis studies those variables regarding most relevant Spanish newspapers (ABC, El Mundo, El País, El Periódico de Catalunya and La Vanguardia) and also national online media (El Confidencial, El Diario.es and Infolibre). Additionally, the results are compared and contrasts with survey data to professionals and informed readers about their perception of aforementioned mass media. Main outcomes reveal significant correspondences between assessments of those surveyed, especially professionals, and data provided by content analysis.